Benefits of prenatal and postnatal vitamin D supplementation (Journal of Medical Science, 2021)
The best evidence for the role of vitamin D in infants is its influence on skeletal growth, however, the pleiotropic actions of vitamin D in the foetus and neonates are under-researched. The systematic reviews, based mostly on observational studies, suggest correlations between prenatal and postnatal supplementation and the occurrence of allergy, respiratory infections, sepsis or mental and behavioural development. Some of these studies focused on subgroups of neonates, such as preterm infants, investigating the influence inter alia on sepsis, bronchopulmonary dysplasia, and necrotising enterocolitis. Currently, there is a need for randomised trials for proof of the skeletal and pleiotropic effects of vitamin D in infants.